KAJIAN NUMERIK DISTRIBUSI UDARA PADA RUANG BER-AC UNTUK MENCAPAI TINGKAT EFISIENSI ENERGI YANG OPTIMAL (Numeric Analysis Of Air Distribution In Air-Conditioned Room To Obtain Optimum Energy Effeciency Level) - Seputra, Jackobus Ade Prasetya (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, Kupang, 2018)
The demand for household energy in Indonesia is dominated by air conditioning sector. One of the efforts to optimize air conditioner (AC) is to figure out the best air distribution pattern. Nowadays, there are three air distribution types of marketed AC; (1) perfect mixing, (2) displacement, and (3) radiant cooling. This research examines the influence of those types toward energy consuption to ensure indoor thermal comfort. It was conducted by conducting literature review, mathematical calculation, and numerical simulation. Based on SNI 03-6572-2001, the research applied comfort criteria of indoor air temperature of 24oC as setpoint with 28.1oC initial temperature. Energy consumption is estimated based on time required to achieve the setpoint. The fastest cooling time is obtained by displacement in 80 seconds, then perfect mixing in 112 seconds, and the longest is radiant cooling in 460 seconds. Energy calculation establishes three scenarios of heat load represented by air con’s idle time; (a) high load, 30 seconds, (b) moderate load, 60 seconds, and (c) low load, 90 seconds. For 300 hours of operational time per month, displacement consumes (a) 148.4, (b) 116.6, and (c) 96 kWh/month, whilst perfect mixing needs (a) 160.9, (b) 132.8, and (c) 113.1 kWh/month. Lastly, radiant cooling spends (a) 191.5, (b) 180.5, and (c) 170.6 kWh/month. Keywords: energy efficiency, air conditioning, air distribution pattern